TACIT AND EXPLICIT KNOWLEDGE MANAGEMENT MODERATED BY LEARNING ORGANIZATION IN AN EFFORTS TO IMPROVE LECTURERS' PERFORMANCE IN WEST JAVA - Windiarti, Sofia; Romi, Mochamad Vrans (SULTANIST: Jurnal Manajemen dan Keuangan, 2024)
The government continues to strive to improve the quality and welfare of teaching staff in higher education. Through Permendikbudristek Number 44 of 2024, the focus is given to more comprehensive regulations related to the profession, career, and income of lecturers. Current conditions According to the Scientific Journal Ranking (SJR), Indonesia is ranked 58th with an H-index of 259. In the Southeast Asia region, Indonesia is still below Singapore (H-index 646), Malaysia (H-index 373), Thailand (H-index 369), and the Philippines (H-index 274), which means that there must be an increase in the performance of lecturers in the tridharma of higher education. The purpose of this study is to create a model for optimizing tacit and explicit knowledge management moderated by a learning organization: a case study of improving the performance of lecturers in West Java. The research method used in this study uses descriptive analysis with quantitative methods. The object of the study is Lecturers at Private Universities in West Java, with the number of samples taken to represent the population of 372 samples with proportional random sampling techniques. Data analysis using structural equation modeling (SEM) data processing through Amos v.22 software. In general, the purpose of this study is to create a model for optimizing tacit and explicit knowledge management moderated by learning organization: a case study of improving the performance of lecturers in West Java. The results of the study show that tacit knowledge and explicit knowledge simultaneously have a positive and significant effect on the performance of lecturers; learning organizations positively strengthen the relationship between tacit knowledge and employee performance; learning organizations positively strengthen the relationship between tacit knowledge and lecturer performance